Application of Alkali Lignin and Spruce Sawdust for the Effective Removal of Reactive Dyes from Model Wastewater - Hajkova, Katerina; Filipi, Michaela; Fojtik, Roman; Dorieh, Ali (MDPI, 2023)
Today, the emphasis is on environmentally friendly materials. Alkali lignin and spruce sawdust are suitable natural alternatives for removing dyes from wastewater. The main reason for using alkaline lignin as a sorbent is the recovery of waste black liquor from the paper industry. This work deals with removing dyes from wastewater using spruce sawdust and lignin at two different temperatures. The decolorization yields were calculated as the final values. Increasing the temperature during adsorption leads to higher decolorization yields, which may be due to the fact that some substances react only at elevated temperatures. The results of this research are useful for the treatment of industrial wastewater in paper mills, and the waste black liquor (alkaline lignin) can be used as a biosorbent.
Aplikace alkalického ligninu a smrkových pilin pro efektivní odstranění reaktivních barviv z modelové odpadní vody
Keywords: alkali lignin; spruce sawdust; reactive dyes; decolorization; alkalický lignin; smrkové piliny; reaktivní barviva; odbarvování